The Cunetio and Normanby hoards - Bland, Roger 1955- (Spink & Son Ltd, 2018)
The Cunetio and Normanby hoards are the two of the largest Roman coin hoards from Britain. They both comprise mostly ?radiate? coins struck in the second half of the 3rd century and are the most important catalogues for people identifying radiate coins in Britain dating from AD 253 to AD 275. 0The Cunetio hoard was originally published as a single volume, 'The Cunetio Treasure by E.M. Besly and R.F. Bland (British Museum Press, 1983). The Normanby hoard was published along with several other hoards in 'The Normanby Hoard and other Roman coin hoards: Coin Hoards from Roman Britain VIII' edited by R.F. Bland and A.M. Burnett (British Museum Press, 1988). This edition provides the two hoards in one volume with a note on more recent work on the radiate coinage of AD 253-96 and notes to aid identification by Sam Moorhead
Keywords: Geschichte 270-286; Geschichte 253-274; Münzfund; Scunthorpe; Mildenhall; Katalog